PREFERENSI PELANGGAN ONLINE SHOP INSTAGRAM BERDASARKAN E-SERVICE QUALITY DENGAN MENGGUNAKAN ANALISIS CLUSTER DAN ANALISIS CONJOINT - Amelindha Vania; Sumiati Sumiati; Fatchur Rohman (Universitas Mercu Buana, 2018)
Abstract. The study aims to determine the most preferred e-service quality attribute chosen by customers and classify customers based on their preferences andsociodemographic characteristics in Malang city. This research used quantitativeapproach with descriptive research. The research objects were 105 respondents ofinstagram online shop customers in Malang selected using quota sampling method. Theanalysis methods used were cluster and conjoint analysis. The results showed thatInstagram online shop customers in Malang were classified into 2 segments; the firstsegment (adults) was college students and employees above 20 years of age with IDR2.5 – 5 million incomes per month. Meanwhile, the second segment (teenagers) washigh school and college students under 20 years of age with less than IDR 1 million permonth revenue. Both segments prioritized fulfillment (product shipments) when theywould like to shop in instagram. The least e-service quality attribute considered bycustomer was efficiency (information efficiency).